2019
DOI: 10.1136/vr.105009
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of perioperative tramadol for canine sterilisation pain management

Abstract: Surgical sterilisation to manage free-roaming dog populations is widely used in many countries. However, few studies have examined optimal postoperative pain management regimens at low-resource, high-throughput veterinary clinics. The aim of this study was to examine the efficacy of two intravenous analgesic regimens, preoperative administration of meloxicam and tramadol, or meloxicam alone, in free-roaming dogs undergoing sterilisation. A total of 125 dogs were included, with 64 dogs in the meloxicam-tramadol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…1 & Table 1). All of the included studies, except one (Meunier et al 2019), had a superiority design, out of which 11 were performed as multiarm trials (Mondal et al 2005;Martins et al 2010;Fajardo et al 2012;Kongara et al 2012;Rialland et al 2012;Davila et al 2013;Morgaz et al 2013;Cardozo et al 2014;Marques 2015;Zhang et al 2017;Ugwu et al 2020) and 14 as parallel trials (Mastrocinque & Fantoni 2003;Carareto et al 2007;Gupta et al 2009;Schuszler et al 2010;Kongara et al 2013;St anescu et al 2013;Centonze et al 2014;Delgado et al 2014;Benitez et al 2015;Oliveira et al 2016;Giudice et al 2017;Saberi Afshar et al 2017;Uscategui et al 2017;Read et al 2019). The mean sample size of the included studies was 33 ± 24 dogs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 & Table 1). All of the included studies, except one (Meunier et al 2019), had a superiority design, out of which 11 were performed as multiarm trials (Mondal et al 2005;Martins et al 2010;Fajardo et al 2012;Kongara et al 2012;Rialland et al 2012;Davila et al 2013;Morgaz et al 2013;Cardozo et al 2014;Marques 2015;Zhang et al 2017;Ugwu et al 2020) and 14 as parallel trials (Mastrocinque & Fantoni 2003;Carareto et al 2007;Gupta et al 2009;Schuszler et al 2010;Kongara et al 2013;St anescu et al 2013;Centonze et al 2014;Delgado et al 2014;Benitez et al 2015;Oliveira et al 2016;Giudice et al 2017;Saberi Afshar et al 2017;Uscategui et al 2017;Read et al 2019). The mean sample size of the included studies was 33 ± 24 dogs.…”
Section: Resultsmentioning
confidence: 99%
“…The mean sample size of the included studies was 33 ± 24 dogs. Sample size was calculated in three of the 26 included studies (Delgado et al 2014;Uscategui et al 2017;Meunier et al 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, according to the Glasgow Composite Measure Pain Scale, nefopam IV at 2 mg/kg conferred superior analgesia than the same dose of tramadol, whereas patients receiving tramadol required less rescue analgesia (1 mg/kg IV of nefopam) [ 57 ]. Furthermore, Meunier et al [ 58 ] reported that the preoperative IV application of 0.2 mg/kg meloxicam and 4 mg/kg tramadol as a multimodal analgesic regimen for free-roaming dogs subjected to OVH provided adequate analgesia but no clinical benefit over the use of meloxicam alone. Interestingly, the need for rescue analgesia was approximately four times greater in animals administered meloxicam than in the opioid group.…”
Section: Therapeutic Efficacy Of Tramadol In Dogsmentioning
confidence: 99%